How do the methodological strategies influence the communicative method in the process of teaching-learning of the english language in children of first grade at Centro Educativo Belen Elementary School,Bugaba's District, 2009? - Pitty A., Doris (UDELAS, 2010)
Through the history pedagogical precursors have been several studies about development of teaching and learning process. Psychologists as Piaget, Bandura, Ausubel and others designed strategic models that became methodological steps used by teachers to transmit knowledge to the students.